IMPLEMENTASI KEBIJAKAN RENTAN ADMINISTRASI KEPENDUDUKAN DI DINAS KEPENDUDUKAN DAN CATATAN SIPIL KABUPATEN HALMAHERA UTARA - BELLA, ANGELA (JURNAL ADMINISTRASI PUBLIK, 2013)
Abstract : Administration vulnerable population population population is experiencing barriers in obtaining documents population caused by natural disasters and social disaster victims. In accordance with the results in dapati masi prasurvei many residents in North Halmahera are still experiencing vulnerable population administration. Therefore it is necessary to conduct further research on the "Implementation of Policies Vulnerable Population Administration in the Department of Population and Civil Registry of North Halmahera.Based on the conclusions of this study, it can be recommended for general advice for North Halmahera district government in this case the Department of Population and Civil Registry of North Halmahera regency that is hoped to North Halmahera district government to be able to follow up on the Minister of Home Affairs Regulation No. 11 of 2010, concerning the implementation of Data Collection and Publishing Guidelines policy document Population Population Share Vulnerable Population Administration to implement, and can also optimize the existing resources in the Department of Population and Civil Registry and add facilities to support the services of the agency itself.